Sharing a smile - Kramar, Nicki (Simon & Schuster Books For Young Readers, 2021)
Sophie is feeling a bit worried about the world and going outside lately means wearing a mask, but she realizes she is not the only one who feels a little scared and decides to spread a small act of kindness in her neighborhood.